2022
DOI: 10.3389/fonc.2022.907520
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for combination of paclitaxel and CDK4/6 inhibitor in ovarian cancer therapy — non-mitotic mechanisms of paclitaxel

Abstract: Taxanes and CDK4/6 inhibitors (CDK4/6i) are two families of successful anti-mitotic drugs used in the treatment of solid tumors. Paclitaxel, representing taxane compounds, has been used either alone or in combination with other agents (commonly carboplatin/cisplatin) in the treatment of many solid tumors including ovarian, breast, lung, prostate cancers, and Kaposi’s sarcoma. Paclitaxel has been routinely prescribed in cancer treatment since the 1990s, and its prominent role is unlikely to be replaced in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…As one of the most effective chemotherapeutic drugs, paclitaxel is popularly applied for the treatment of solid tumors for example breast cancer, ovarian cancer, and non-small cell lung carcinoma. 54,55,56 Of note, dorsal root ganglion (DRG) infiltration by macrophages contributes to paclitaxel-induced peripheral neuropathy through activating Toll-like receptor 4 (TLR4) and upregulating monocyte chemotactic protein 1 (MCP-1) expression, which for the first time stresses a mechanistic link that TLR4 activation followed by MCP-1 elevation by DRG neurons leads to macrophage infiltration to the DRG during the development of behavioral signs of CIPN. 57 Moreover, Old et al have reported vincristine sulfate (VCR) treatment can improve the adhesion property of endothelial cells, leading to the infiltration of circulating CX3CR1 + monocytes into the sciatic nerve, which has been observed for a murine model of vincristine-induced neuropathic pain.…”
Section: Role Of Tumor-associated Macrophages In Cancer-related Neuro...mentioning
confidence: 99%
“…As one of the most effective chemotherapeutic drugs, paclitaxel is popularly applied for the treatment of solid tumors for example breast cancer, ovarian cancer, and non-small cell lung carcinoma. 54,55,56 Of note, dorsal root ganglion (DRG) infiltration by macrophages contributes to paclitaxel-induced peripheral neuropathy through activating Toll-like receptor 4 (TLR4) and upregulating monocyte chemotactic protein 1 (MCP-1) expression, which for the first time stresses a mechanistic link that TLR4 activation followed by MCP-1 elevation by DRG neurons leads to macrophage infiltration to the DRG during the development of behavioral signs of CIPN. 57 Moreover, Old et al have reported vincristine sulfate (VCR) treatment can improve the adhesion property of endothelial cells, leading to the infiltration of circulating CX3CR1 + monocytes into the sciatic nerve, which has been observed for a murine model of vincristine-induced neuropathic pain.…”
Section: Role Of Tumor-associated Macrophages In Cancer-related Neuro...mentioning
confidence: 99%
“…It activates signaling pathways that promote apoptotic cell death, leading to the elimination of abnormal cells. This apoptotic effect is thought to contribute to the reduction of endometriotic lesions (Li et al, 2022;Okimura et al, 2018;Smith et al, 2022).…”
Section: Phytochemicals Reported For Management Of Endometriosismentioning
confidence: 99%
“…However, the use of a single chemotherapy drug does not achieve the desired effect [4,5], and long-term use of chemotherapy drugs is also prone to drug resistance [6,7]. Therefore, for the treatment of patients with advanced tumours, a combination of multiple drugs is often applied [8][9][10]. Additionally, the combined therapy strategy not only helps increase the efficacy of chemotherapeutics, but also decreases the dosage of the drugs, as prolonged and high-dose chemotherapy is easily associated with safety issues among clinical trial patients including asthenia, cutaneous reactions, hematological issues and neurosensory reactions [11,12].…”
Section: Introductionmentioning
confidence: 99%